Eff ect of propiconazole and salicylic acid on the growth and photosynthetic pigments in Sorghum bicolor (L.) Moench. under drought condition - Arivalagan, Maruthaiya; Somasundaram, Ramamurthy G (Journal of Ecobiotechnology, 2016)
The present investigations were carried out to estimate the morphological, pigments variation and ameliorating effect of propiconazole (PCZ) and salicylic acid (SA) on drought stress in sorghum (Sorghum bicolor L. Moench.) Var. CO-30. A 30 days after sowing (DAS), the plants were subjected to 3, 6, and 9 days interval drought stress and drought with PCZ at 1 mM and drought with SA at 1 mM at 30, 40, and 50 DAS. The plants irrigated regularly in alternate day interval were kept as control. The plant samples were collected on 60, 70, and 80 DAS from all the treatments. The root length, shoot length, fresh weight, dry weight, total leaf area, and photosynthetic pigment estimation was carried out in each treatment. Individual and combined drought stress with PCZ and SA treatments increased the root length when compared to control. The PCZ and SA treatments mitigated the drought stress by increasing the morphological and pigment contents and there by the way for overcoming drought stress in S. bicolar plants.